(untitled) (Eduscotech, 2023)
This study aims to improve language skills in 5-year-old children at TK Ngawi through the application of storytelling as an interactive and enjoyable learning strategy. The research employs Classroom Action Research with two cycles involving observation, implementation of storytelling activities, and reflection on the learning outcomes. The subjects were 20 children from the TK B group. During storytelling sessions, the teacher used various supporting media such as puppets, illustrative pictures, and props to capture the children’s interest and attention. The children were encouraged not only to listen attentively but also to actively participate by imitating stories and confidently retelling them orally. The results indicate that storytelling significantly enhances vocabulary acquisition, the ability to construct coherent narratives, and increases the children’s confidence in verbal communication in front of peers. This improvement is evidenced by the rise in average language proficiency test scores from the pre-cycle to the second cycle. Moreover, the interactive and enjoyable learning atmosphere motivates children to be more active participants in language learning. Success factors include the teacher’s storytelling skills, varied learning media, and parental support reinforcing language stimulation at home. Therefore, storytelling is not only effective in enhancing language ability but also plays a vital role in developing children’s courage and motivation in oral communication. The study recommends the regular implementation of storytelling as a language teaching strategy in kindergarten, emphasizing the need for enriched storytelling media and active parental involvement at home